Menjelajahi Pemikiran Politik Nurcholis Madjid Tentang Agama dan Negara - Rasyidin, Yusafrida (Universitas Islam Negeri Raden Intan Lampung, 2020)
Abstract: Nurcholish Madjid is a prominent Muslim scholar and thinker who has national-minded ideas. One of his views on the relationship between religion and state. This thought, although it was controversial when it was first raised, it had a great influence on the national and Islamic discourse in Indonesia. In the relationship of religion and state Nurcholish argues that religion and state cannot be separated, because religion is the basis of life and becomes the culture of community life in the state, but Nurcholish Madjid strongly rejects the concept of an Islamic state, especially in the context of Indonesianism. Because according to him the Islamic State is a distortion of proportional relations between religion and the state. Therefore an Islamic state is neither a religious state nor a secular state.Keywords: Nurcholish Madjid, Politics, Religion and Country Abstrak: Nurcholish Madjid merupakan salah seorang tokoh cendikiawan dan pemikir muslim yang mempunyai gagasan-gagasan yang berwawasan kebangsaan. Salah satu pandangannya tentang hubungan agama dan negara. Pemikirannya ini, walaupun mendapat kontroversial ketika pertama kali dilontarkannya, namun mempunyai pengaruh besar terhadap wacana kebangsaan dan keislaman di Indonesia. Dalam hubungan agama dan negara Nurcholish berpendapat bahwa agama dan negara tidak dapat di pisahkan, karena agama merupakan landasan hidup dan menjadi kultur kehidupan masyarakat dalam bernegara, namun Nurcholish Madjid menolak tegas konsep negara Islam, terutama dalam konteks keindonesiaan. Karena menurut beliau Negara Islam merupakan distorsi hubungan proposional antara agama dan negara. Oleh karena itu negara Islam bukanlah negara agama dan bukan pula negera sekuler.Kata Kunci: Nurcholish Madjid, Politik, Agama dan Negara